2009
DOI: 10.1016/j.fertnstert.2008.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol modulation of hepatocyte growth factor by stromal fibroblasts in the female reproductive tract

Abstract: NARRATIVE ABSTRACT Primary human uterine, cervical and ectocervical stromal fibroblasts constitutively secrete hepatocyte growth factor (HGF); yet only uterine stromal fibroblasts increase HGF secretion in response to estradiol. Estradiol-induced HGF secretion by uterine stromal fibroblasts may have significant impact on uterine cancer and endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Sugawara et al also identified HGF as a critical factor in E 2 -mediated regulation of human uterine ECs (Sugawara et al, 1997). E 2 treatment of human primary uterine stromal fibroblasts results in increased secretion of HGF (Coleman et al, 2009(Coleman et al, , 2012, which implies a functional relationship between E 2 and HGF. In addition to similarities between endogenous HGF and E 2 in normal FRT physiology, there is a correlation between reproductive tissue cancers and endometriosis and relatively high E 2 concentrations with increased HGF levels (Haslam and Woodward, 2003;Khan et al, 2005;Matsumoto and Nakamura, 2006).…”
Section: Figure 5 Effect Of Epithelial Cell (Ec) Co-culture With Stromentioning
confidence: 97%
See 1 more Smart Citation
“…Sugawara et al also identified HGF as a critical factor in E 2 -mediated regulation of human uterine ECs (Sugawara et al, 1997). E 2 treatment of human primary uterine stromal fibroblasts results in increased secretion of HGF (Coleman et al, 2009(Coleman et al, , 2012, which implies a functional relationship between E 2 and HGF. In addition to similarities between endogenous HGF and E 2 in normal FRT physiology, there is a correlation between reproductive tissue cancers and endometriosis and relatively high E 2 concentrations with increased HGF levels (Haslam and Woodward, 2003;Khan et al, 2005;Matsumoto and Nakamura, 2006).…”
Section: Figure 5 Effect Of Epithelial Cell (Ec) Co-culture With Stromentioning
confidence: 97%
“…In contrast, TNF-α and macrophage inhibitory protein (MIP)-3α/CCL20 secretion by uterine ECs is regulated indirectly by fibroblast cell secretion of growth factors such as hepatocyte growth factor (HGF) (Grant-Tschudy and Wira, 2005b). After E 2 treatment, uterine fibroblasts up-regulate the production of HGF, which in turn induces TNF-α and MIP-3α/CCL20 secretion (Grant-Tschudy and Wira, 2005b;Coleman et al, 2009;Haddad and Wira, 2010). E 2 can reduce the proinflammatory cytokine response after stimulation with pathogen ligands (via Toll-like receptors).…”
Section: Influence Of Sex Hormones On Cytokines Chemokines and Antimmentioning
confidence: 99%
“…Intriguingly, the withdrawal of sex hormones from uterine stromal fibroblasts treated with E 2 and P4 for several days in vitro, increases their secretion of proinflammatory cytokines including IL-6, CCL2, CXCL8 and IFNα amongst others 50 . Because epithelial-stromal cell interactions are essential in facilitating hormone-induced growth and development in the EM, we examined the effects of E 2 on hepatocyte growth factor (HGF) made by FRT fibroblasts and found that secretion is regulated by E 2 in the EM, but not in Cx and Ecx 51, 52 . Given that HGF regulates epithelial cell (EC) tight junction barrier integrity, these findings indicate that sex hormones mediate communication between fibroblasts and epithelial cells with potential consequences for HIV acquisition.…”
Section: Contribution Of Stromal Fibroblasts To the Frt Environmentmentioning
confidence: 99%
“…The mucosal immune system in the FRT contains a spectrum of immune cells including NK cells, neutrophils, macrophages and T cells that are different from their blood counterparts al 3,4,52, 53 . In addition to their unique phenotypic characteristics, these cells are functionally unique and responsive to changes in hormone balance during the menstrual cycle 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the activation of a wide variety of ligands, including fibroblast growth factor, transforming growth factor-␤, epidermal growth factor, vascular endothelial growth factor, and hepatocyte growth factor (HGF) and its receptor MET, upregulates the expression of EMT-regulating transcription factors (26). Among these ligands, many actions of HGF are mirrored by estradiol in the female reproductive tract, and several investigators have reported a relationship between HGF and estradiol in the pathology of female genital disease (8,31,36).…”
mentioning
confidence: 99%